Comfort Working with Superiors, Comfort Working with Peer Employees, and a Sense of Company Unity to Employee Work Motivation - Simangunsong, Elisabeth; Sitanggang, Darna (Dinasti Publisher, 2023)
The purpose of this study was to determine the Effect of Comfort Working with Superiors, Comfort Working with Peers and Sense of Company Unity on Employee Work Motivation at PT Sanfremy Pratama. The research method uses Random Sampling with a sample size of 67 employees. The results obtained are partially Comfort Working with Superiors has a positive and significant effect on Employee Work Motivation at PT Sanfremy Pratama. Partially, Comfort Working with Peers has a positive and significant effect on Employee Work Motivation at PT Sanfremy Pratama.Partially, Sense of Company Unity has a positive and significant effect on Employee Work Motivation at PT Sanfremy Pratama.Simultaneously, Comfort Working with Superiors, Comfort Working with Peers, Sense of Company Unity have a positive and significant effect on Employee Work Motivation at PT Sanfremy Pratama.Based on the results of the adjusted coefficient of determination test, the adjusted R square value is 0.727. This shows that 72.7% of the variables of Comfort Working with Superiors (X1), Comfort Working with Peers (X2), and Sense of Company Unity (X3) are able to explain the variable Employee Work Motivation (Y) at PT Sanfremy Pratama while the remaining 27.3% is the influence of other independent variables that are not explained by the research model such as work stress variables, job appraisal and intrinsic motivation